ChemInform Abstract: The Development of a Modular Synthesis of Teraryl‐Based α‐Helix Mimetics as Potential Inhibitors of Protein—Protein Interactions. Issue 36 (9th September 2014) - Trobe, Melanie; Peters, Martin; Grimm, Sebastian H.; Breinbauer, Rolf
Abstract Review: [35 refs.